2022
DOI: 10.1177/10668969221081729
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Clear Cell Renal Cell Carcinoma Involving the Thyroid Gland: A Clinicopathologic Study of 17 Patients

Abstract: Context. Metastatic clear cell renal cell carcinoma (RCC) is one of the most common secondary thyroid malignancies. Diagnosis can be challenging, particularly if presenting many years after initial diagnosis. We reviewed clinicopathologic features and immunoprofile of metastatic clear cell RCC in thyroid. Design. We identified 17 patients from 2003-2021. Clinical data were obtained from medical records, and slides were retrieved and reviewed. Results. Seventeen patients (12 male and 5 female) included 12 thyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 46 publications
1
7
1
Order By: Relevance
“…[17][18][19][22][23][24][25] The male-to-female ratio was 1:1.2, 18 This is the largest similar series reported in recent years. In contrast to previous studies, renal clear cell carcinoma with metastasis to the thyroid gland, which has been reported more frequently before, 4,8,17,23,25 was not found in our study, and it also did not include any sarcoma, which may be a bias caused by our sample size.…”
Section: Epidemiologic and Ultrasonographic Features Of Smtgcontrasting
confidence: 96%
See 2 more Smart Citations
“…[17][18][19][22][23][24][25] The male-to-female ratio was 1:1.2, 18 This is the largest similar series reported in recent years. In contrast to previous studies, renal clear cell carcinoma with metastasis to the thyroid gland, which has been reported more frequently before, 4,8,17,23,25 was not found in our study, and it also did not include any sarcoma, which may be a bias caused by our sample size.…”
Section: Epidemiologic and Ultrasonographic Features Of Smtgcontrasting
confidence: 96%
“…Secondary malignancies of thyroid gland (SMTG) are uncommon, with an incidence of 1.25%–24% in autopsy series, 2 and 1.4%–3% in all patients operated on for thyroid malignancies 3 . Secondary tumors most commonly involving the thyroid gland include tumors of the pharynx, larynx, esophagus, and mediastinum, and sources of distant metastatic tumors, include the kidney, lung, breast, and gastrointestinal tract 4–10 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, a panel of stains must be used to guide the diagnosis. It has been suggested that positivity for CAIX, PAX-8 and negativity for TTF-1, TG and keratin 7 are supportive of metastatic RCC when found in the thyroid gland (19). Our patient's staining pattern was PAX-8(+)/TG(-)/TTF-1(-) supported RCC as the origin of the specimen.…”
Section: Discussionsupporting
confidence: 57%
“…TTM is extremely rare. However, TTM in MRCCT is not a rare phenomenon and can occur in thyroid neoplasms, such as follicular adenoma, follicular variant of papillary thyroid carcinoma, and noninvasive follicular thyroid neoplasm with papillary‐like nuclear features 8,10,20–23 . Heffess et al reported that 27.8% of MRCCT metastasized into adenomatous nodules or follicular adenoma 10 .…”
Section: Discussionmentioning
confidence: 99%